2004
DOI: 10.1091/mbc.e04-08-0750
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Microtubule Flux during Metaphase and Anaphase in Crane-Fly Spermatocytes

Abstract: Microtubule flux in spindles of insect spermatocytes, long-used models for studies on chromosome behavior during meiosis, was revealed after iontophoretic microinjection of rhodamine-conjugated (rh)-tubulin and fluorescent speckle microscopy. In time-lapse movies of crane-fly spermtocytes, fluorescent speckles generated when rh-tubulin incorporated at microtubule plus ends moved poleward through each half-spindle and then were lost from microtubule minus ends at the spindle poles. The average poleward velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 42 publications
5
75
0
Order By: Relevance
“…8) has provided important insights into the dynamic organization of meiotic spindle microtubules. It has been shown that both kMTs and non-kMTs flux poleward, but at different rates (9)(10)(11)(12). More recently, it has been shown that microtubule flux rate changes across the length of metaphase meiotic spindle (13).…”
mentioning
confidence: 99%
“…8) has provided important insights into the dynamic organization of meiotic spindle microtubules. It has been shown that both kMTs and non-kMTs flux poleward, but at different rates (9)(10)(11)(12). More recently, it has been shown that microtubule flux rate changes across the length of metaphase meiotic spindle (13).…”
mentioning
confidence: 99%
“…This poleward microtubule 'flux' is coupled to minus end disassembly at or near the poles [23,[26][27][28][29][30][31][32]. Anaphase A in these cells is therefore a superposition of a kinetochore's pac-man movement relative to the microtubules and the microtubules' flux relative to the poles.…”
Section: Kinetochore-attached Microtubules Can 'Flux' Continuously Tomentioning
confidence: 99%
“…For example, in crane fly spermatocytes, Flux occurs at nearly twice the rate of anaphase A, since the plus-ends of kinetochore microtubules continue to polymerize even as the kinetochore is pulled poleward (LaFountain et al 2004). Similarly in Xenopus egg extract spindles, the rates of Flux and anaphase A are almost identical (Desai et al 1998).…”
Section: Mechanism Of Flux I: Depolymerization Of Spindle Pole-focusementioning
confidence: 99%